Summary writing in a Thai EFL university context - Kim McDonough (2018)
Previous research has shown that L2 writers experience difficulty writing summaries of texts in ways that avoid direct copying or superficial modifications to source text sentences, but fewer studies have explored whether summary writing instruction leads to improved textual appropriation. The current study analyzes three summary paragraphs written by Thai EFL university students ( N= 46) during a 17-week EFL writing class that included explicit instruction in paragraph writing and paraphrasing strategies. Their texts were analyzed in terms of the rhetorical organization of a summary paragraph and the incorporation of source text information. The findings revealed a significant increase in the number of students who explicitly referenced the source texts, along with significant changes in the occurrence of copied and modified word strings. Considerations for the use of summary writing in EFL settings are discussed. © 2014 Elsevier Inc.